The Influence of Work Stress Compensation and Job Satisfaction on Nurse Turnover Intention at General Hospital Sinar Husni Medan - Indry Metami Hutabarat; Santi Rizki (Green Inflation: International Journal of Management and Strategic Business Leadership, 2024)
This study aims to determine Job Stress partially has a significant effect on Nurse Turnover Intention at Sinar Husni Medan Hospital, to determine Compensation partially has a positive and significant effect on Nurse Turnover Intention at Sinar Husni Medan Hospital, Job Satisfaction partially has a positive and significant effect on Nurse Turnover Intention at Sinar Husni Medan Hospital. The method used in this research is quantitative which analyzes and tests with data using numbers with instrument tools, classical assumption tests, multiple linear regression tests, hypothesis tests, and determination tests. Research results: Partially Job Stress is positive and significant to Turnover intention, partially Compensation has an effect on Turnover Intentuon, partially Job Satisfaction has a positive and significant effect on Turnover Intention, simultaneously Job Stress, Compensation and Job Satisfaction have a positive and significant effect on Turnover Intention.